The first report of chemical and biological study of essential oil from Begonia reniformis leaf (Begoniaceae) - da Silva, Anne G. M.; Silva, Marcilio W. F.; Bezerra, Giselle B.; Ramos, Clécio Souza (Eclética Química, 2017)
Species of the genus Begonia are expensive ornamental plants. There have been few reports of chemical studies with the Begonia species. Here we report the first chemical and biological study of essential oil for a species of Begonia. The essential oil of the Begonia reniformis leaf obtained by hydrodistillation was analyzed via GC-MS and twenty-one compounds were identified. Sesquiterpenes silphiperfol-4,7(14)-diene and β-vetispirene were the major ones with a percentage of 15.7 and 21.0%, respectively. The oil showed weak activity against bacteria Bacillus subtilis and Pseudomonas aeruginosa with minimum inhibitory concentrations of 625μg/mL for each of the two bacteria.